The effect of corporate ethical misconduct on JSE-listed companies’ returns - Luthuli, Makhosazane; Moloi, Tankiso (International Journal of Management and Sustainability, 2024)
The purpose of the study was to determine the relationship between corporate misconduct announcements and share prices. The study employed an event study methodology where data was collected from a sample of 30 companies that were listed on the Johannesburg Stock Exchange (JSE). Data collected spanned a period of ten years, from 2011 to 2020. The study’s findings demonstrate that there is no significant relationship between announced incidents of ethical misconduct by JSE-listed companies and the returns of the underlying shares. Previous studies of a similar nature have asserted that the announced ethical misconduct of a company has a significantly negative effect on its share price. The study considers the dynamics that exist between principals (shareholders) and their agents (directors), who are charged with the governance of listed companies. It considers the morality of the actions taken by agents in governing organisations and the implications for the equity returns of principals. Contrary to the previous studies and studies in other countries, analysed results imply that equity holders of JSE-listed companies do not significantly punish companies that have incidents of ethical misconduct that are announced. The study’s findings have practical implications for the JSE and its requirements for disclosure of ethical issues to firm principals.